Indonesia Journalistic Code of Ethics (News Aggregation Study) - Erawaty, Dyah Permana; Irwansyah, nfn (Jurnal Pekommas, 2019)
News aggregation is the process of taking news from published sources, reshaping it, and publishing it as a new news. News aggregation becomes an important part of journalism. This research intends to examine whether the news aggregation complies with journalistic principles in Indonesia or not. The significance of this research for the Indonesian community is that they understand the news aggregation in the context of Indonesian journalism. This research used a qualitative approach in the post-positivist paradigm. Data was collected by narrative literature review and interviews. The informants were the expert from the Indonesia Press Council. In addition, to see trends in the qualitative use of news aggregations, interviews were conducted with three news aggregation users. The analysis resulted that the news aggregator is not a journalistic media, because it has not yet met the criteria of Indonesian Law no. 40 of 1999 concerning the Press, as well as the Cyber Media guidelines. The news aggregator content are news and opinions those were collected from the press media and social media. Even though the news aggregators content was not believed to be true, smartphone users will continue to use it.